On the Dynamics of Abstract Retarded Evolution Equations - Desheng Li; Jinying Wei; Jintao Wang (Abstract and Applied Analysis)
This paper is concerned with the dynamics of the following abstract retarded evolution equation: in a Hilbert space , where is a self-adjoint positive-definite operator with compact resolvent and is a locally Lipschitz continuous mapping. The dissipativity and pullback attractors are investigated, and the existence of locally almost periodic solutions is established.